The effects of previous open renal stone surgery types on PNL outcomes - Ozgor, Faruk; Kucuktopcu, Onur; Ucpinar, Burak; Sarilar, Omer; Erbin, Akif; Yanaral, Fatih; Sahan, Murat; Binbay, Murat (Canadian Urological Association Journal, 2016)
Introduction: Our aim was to demonstrate the effect of insicion of renal parenchyma during open renal stone surgery (ORSS) on percutaneous nephrolithotomy (PNL) outcomes. Methods: Patients with history of ORSS who underwent PNL operation between June 2005 and June 2015 were analyzed retrospectively. Patients were divided into two groups according to their type of previous ORSS. Patients who had a history of ORSS with parenchymal insicion, such as radial nephrotomies, anatrophic nephrolithotomy, lower pole resection, and partial nephrectomy, were included in Group 1. Other patients with a history of open pyelolithotomy were enrolled in Group 2. Preoperative characteristics, perioperative data, stone-free status, and complications were compared between the groups. Stone-free status was defined as complete clearance of stone(s) or presence of residual fragments smaller than 4 mm. The retrospective nature of our study, different experience level of surgeons, and lack of the evaluation of anesthetic agents and cost of procedures were limitations of our study. Results: 123 and 111 patients were enrolled in Groups 1 and 2, respectively. Preoperative characteristics were similar between groups. In Group 1, the mean operative time was statistically longer than in Group 2 (p=0.013). Stone-free status was significantly higher in Group 2 than in Group 1 (p=0.027). Complication rates were similar between groups. Hemorrhage requiring blood transfusion was the most common complication in both groups (10.5% vs. 9.9%). Conclusions: Our study demonstrated that a history of previous ORSS with parenchymal insicion significantly reduces the success rates of PNL procedure.